Polymer-based composite dielectric and preparation method and application thereof

By generating inorganic fillers in a polymer matrix in situ, the problem of difficulty in simultaneously increasing the dielectric constant and breakdown field strength of polymer-based composite dielectric materials in the prior art is solved, and the high dielectric constant, breakdown strength and high temperature energy storage performance are improved, while maintaining good processing performance and suitable conditions for large-scale industrial production.

CN119955133APending Publication Date: 2025-05-09SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411939399.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

While improving the dielectric constant and energy density, existing polymer-based composite dielectric materials are difficult to maintain good processing performance and suitable for large-scale industrial production, and dielectric constant and breakdown field strength performance are difficult to improve at the same time.

Method used

The obtained polymer matrix composite dielectric material is prepared by combining the polymer matrix with a suitable filler precursor and the filler precursor is allowed to form an inorganic filler under heat treatment conditions. This method is simple in process, easy to obtain raw materials, and low in cost. It is suitable for the preparation of a variety of polymer-based composite dielectrics.

Benefits of technology

It significantly improves the dielectric constant and breakdown strength of polymer-based composite dielectric materials, breaks through the dielectric-breakdown inverted coupling relationship, improves high-temperature energy storage performance, and is compatible with industrial large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119955133A_ABST
    Figure CN119955133A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dielectric energy storage materials, in particular to a polymer-based composite dielectric and a preparation method and application thereof. The preparation method comprises the following steps: providing a polymer matrix and a filler precursor; dissolving the polymer matrix in a solvent, adding the filler precursor, and stirring to obtain a mixture solution; and coating the mixture solution on a substrate, and performing heat treatment to enable the filler precursor to generate an inorganic filler in situ in the polymer matrix, thereby obtaining the polymer-based composite dielectric. The method is simple in process, raw materials are easy to obtain, cost is low, stability is high, the dispersity of the prepared polymer-based composite dielectric is obviously improved, meanwhile, the polymer-based composite dielectric has high dielectric constant and breakdown strength, the dielectric-breakdown inversion coupling relation is broken through, the high-temperature energy storage performance is obviously improved, and the polymer-based composite dielectric can be compatible with industrial large-scale production and has wide application prospects. And a feasible solution is provided for research and development of a high-energy-storage-density dielectric material with practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dielectric energy storage materials, and in particular to a polymer-based composite dielectric and a preparation method and application thereof. Background Art

[0002] Film capacitors are characterized by their ultra-fast charging and discharging speed (microseconds), ultra-high power density (up to 10 7 ~10 8 W / kg) and high safety, it has become a key electronic component in advanced electronic power systems and is widely used in smart grid frequency modulation, electric vehicles, and electromagnetic pulse weapons. As an ideal dielectric material, polymer film has gradually become the preferred material for film capacitors due to its advantages such as flexibility, thinness, easy processing, low cost, high operating voltage, and stability and reliability. However, polymer materials generally have the defect of low dielectric constant (<10), which seriously limits the energy density of film capacitors. For example, the current commercial biaxially stretched polypropylene (BOPP) dielectric film has a dielectric constant of only 2.2 and an energy density of only 2 to 5 J / cm 3 , which is much lower than the energy density of batteries and electrochemical capacitors (>20J / cm 3 ). Due to insufficient energy density, the volume and weight of film capacitors in the entire electronic power system often account for more than 25%, which greatly hinders the miniaturization and integration of power devices and power systems. Therefore, the development of polymer dielectric materials with high dielectric constant and high energy density has become an urgent and important research direction.

[0003] The energy storage density of dielectric materials (U e) is proportional to the square of its dielectric constant (K) and electric field strength (E). According to the classic "polymer-filler" two-phase dielectric theoretical model, by introducing ceramic fillers (such as BaTiO3, SrTiO3, etc.) with high dielectric constant (>100), high content (>10vol%) and large size (>100nm) into the polymer matrix, the dielectric constant of the composite dielectric material can be improved, thereby improving its energy storage performance. However, there is a dielectric mismatch between the polymer and the ceramic filler, as well as poor dispersibility of the ceramic filler, which often leads to increased conductivity loss and decreased breakdown field strength of the composite dielectric, thereby limiting the improvement of its energy density. In addition, the introduction of high-content and large-size inorganic fillers will also damage the mechanical properties of the polymer, increase the difficulty of processing, and make it unsuitable for large-scale industrial production. In addition, patent application CN112789326A discloses a method for preparing a high-temperature energy storage hybrid polyetherimide dielectric film, by reacting a hydroxyl-bearing polyetherimide monomer to generate a polyetheramide acid solution with a hydroxyl end group or a side chain, and then adding water and a metal alkoxide to form a uniform sol, and then coating and thermal imidization to obtain a dielectric film. The inorganic phase achieves good dispersion during the hybridization process, improves the interfacial compatibility with the organic phase, improves the energy storage performance of the film at high temperature, enhances the breakdown strength, and improves the glass transition temperature and other properties. However, this method is to add a metal alkoxide solution to a polyetheramide acid solution with a hydroxyl end group or a side chain to form a hybrid inorganic filler / polyetheramide acid slurry, and then obtain a dielectric film by coating and thermal imidization. The strict material selection greatly limits its application range. And it must be pre-chemically treated with a specific polymer monomer before it can be combined with an inorganic filler, and the preparation process is complicated, which is not conducive to industrial production. More importantly, this method does not improve the dielectric constant of the dielectric film.

[0004] Therefore, there is an urgent need to develop a simpler and more effective method for preparing composite dielectric materials that can break the inverted relationship between the dielectric constant and the breakdown field strength in polymer composite dielectrics, and maintain good processing capabilities while improving the energy density, thereby solving the technical bottleneck of large-scale production. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a polymer-based composite dielectric and a preparation method and application thereof, aiming to solve the problems of the existing polymer-based composite dielectric preparation method having strict material selection and complex preparation process, and difficulty in simultaneously improving the dielectric constant and breakdown field strength performance of the composite dielectric.

[0006] The technical solution of the present invention is as follows:

[0007] The first aspect of the present invention provides a method for preparing a polymer-based composite dielectric, which comprises the steps of:

[0008] S1, providing a polymer matrix and a filler precursor;

[0009] S2, dissolving the polymer matrix in a solvent, adding the filler precursor, and stirring to obtain a mixture solution;

[0010] S3, coating the mixture solution on a substrate, and then subjecting the substrate to heat treatment so that the filler precursor generates inorganic fillers in situ in the polymer matrix, thereby preparing the polymer-based composite dielectric.

[0011] Optionally, the weight proportion of the filler precursor in the polymer matrix is ​​0.1 wt% to 3 wt%.

[0012] Optionally, the polymer matrix is ​​at least one of polyimide, polyetherimide, polycarbonate, polyfluorene ester, polypropylene, cycloolefin copolymer, polymethyl methacrylate, polyphenylene sulfide, polyamide-imide, polyaryletherurea and polymethylpentene.

[0013] Optionally, the filler precursor is at least one of aluminum chloride hexahydrate, magnesium chloride hexahydrate, zirconium oxychloride octahydrate, lanthanum chloride hexahydrate, titanium chloride, hafnium chloride, yttrium acetate, zinc acetate dihydrate, tantalum ethoxide, aluminum nitrate nonahydrate, tetramethoxysilane, tetraethoxysilane, zinc 2-ethylhexanoate, cadmium dichloride (bis[diphenylthiourea]), sodium sulfide and cadmium acetate; the inorganic filler is at least one of aluminum oxide, magnesium oxide, zirconium dioxide, lanthanum trioxide, titanium dioxide, hafnium dioxide, yttrium trioxide, zinc oxide, tantalum trioxide, silicon dioxide, zinc sulfide, cadmium sulfide, zinc hydroxide and magnesium hydroxide.

[0014] Optionally, the solvent is at least one of N,N-dimethylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

[0015] Optionally, the heat treatment process is: under air conditions, the heat treatment temperature is 100° C. to 400° C., and the heat treatment time is 1 h to 12 h.

[0016] A second aspect of the present invention provides a polymer-based composite dielectric, which is prepared using the preparation method of the present invention.

[0017] Optionally, the polymer-based composite dielectric comprises a polymer matrix and an inorganic filler, and the volume fraction of the inorganic filler in the polymer-based composite dielectric is 0.1% to 3%.

[0018] Optionally, the inorganic filler is nanoparticles, and the average particle size of the nanoparticles is 10 nm to 50 nm.

[0019] The third aspect of the present invention provides an application of the polymer-based composite dielectric of the present invention in energy storage capacitors, flexible electronic devices or high-frequency circuits.

[0020] Beneficial effects: The present invention combines a suitable polymer matrix and a filler precursor, and the filler precursor undergoes an in-situ chemical reaction in the polymer matrix under heat treatment conditions to generate an inorganic filler, thereby obtaining a polymer-based composite dielectric. The method of the present invention has a simple process, readily available raw materials, low cost, and high stability. The prepared polymer-based composite dielectric has significantly improved dispersibility, high dielectric constant and breakdown strength, breaks through the dielectric-breakdown inversion coupling relationship, significantly improves high-temperature energy storage performance, and is compatible with industrial large-scale production, providing a feasible solution for the research and development of high energy storage density dielectric materials with practical application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A flow chart of a method for preparing a polymer-based composite dielectric provided by the present invention.

[0022] Figure 2 This is a comparison chart of the energy storage performance of the dielectric films prepared in Example 1, Comparative Example 1 and Comparative Example 2.

[0023] Figure 3 This is a comparison chart of the energy storage performance of the dielectric films prepared in Example 2, Comparative Example 2 and Comparative Example 3.

[0024] Figure 4 This is a comparison chart of the energy storage performance of the dielectric films prepared in Example 3, Comparative Example 2 and Comparative Example 4. DETAILED DESCRIPTION

[0025] The present invention provides a polymer-based composite dielectric and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0026] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a polymer-based composite dielectric, which includes the steps of:

[0027] S1, providing a polymer matrix and a filler precursor;

[0028] S2, dissolving the polymer matrix in a solvent, adding the filler precursor, and stirring to obtain a mixture solution;

[0029] S3, coating the mixture solution on a substrate, and then subjecting the substrate to heat treatment so that the filler precursor generates inorganic fillers in situ in the polymer matrix, thereby preparing the polymer-based composite dielectric.

[0030] The embodiment of the present invention combines a suitable polymer matrix and a filler precursor, and the filler precursor undergoes an in-situ chemical reaction in the polymer matrix under heat treatment conditions to generate an inorganic filler, thereby obtaining a polymer-based composite dielectric film (a polymer matrix doped with an inorganic filler at a low volume fraction). The method of the embodiment of the present invention has a simple process, readily available raw materials, low cost, high stability, and is suitable for the preparation of a variety of polymer-based composite dielectrics. Compared with the existing composite dielectric preparation technology, the preparation method provided by the embodiment of the present invention can effectively control the size, uniformity and dispersibility of inorganic filler nanoparticles, thereby solving the problems of performance stability and large-scale processing of composite dielectric materials; at the same time, during the in-situ growth of inorganic filler nanoparticles, the polymer molecular chains directly act as surface modifiers of the nanoparticles, and the problems of surface defects and interface voids of the nanoparticles can be solved without the need for additional organic modification molecules; in addition, there is sufficient interaction between the polymer molecular chains and the nanoparticles, an effective two-phase interface is constructed, and the dielectric enhancement effect is further enhanced. The preparation method provided by the embodiment of the present invention not only successfully overcomes the dispersion problem faced by traditional composite dielectrics, but also breaks through the dielectric-breakdown inversion coupling relationship, significantly improving its room temperature and high temperature energy storage performance, thereby helping to reduce the size and weight of capacitors, reduce energy consumption and improve efficiency, and promote the application of capacitors in harsh environments such as new energy vehicles, aerospace, underground oil and gas exploration, solar power generation and other fields. The prepared composite dielectric film is also compatible with industrial large-scale production, has the advantages of low cost and high stability, and brings broader application prospects for high-performance film capacitors.

[0031] In some embodiments, the weight ratio of the filler precursor in the polymer matrix is ​​0.1 wt% to 3 wt%. By designing the weight ratio of the filler precursor in the polymer matrix within this range, a composite dielectric material with high dielectric constant and high breakdown strength can be obtained, while not compromising the mechanical properties and large-scale processing capability of the polymer.

[0032] In some embodiments, the polymer matrix is ​​at least one of polyimide (PI), polyetherimide (PEI), polycarbonate (PC), polyfluorene ester (FPE), polypropylene (PP), cyclic olefin copolymer (COC), polymethyl methacrylate (PMMA), polyphenylene sulfide (PPS), polyamideimide (PAI), polyaryletherurea (PEEU) and polymethylpentene (PMP).

[0033] In some embodiments, the filler precursor is a chloride, a nitrate, an acetate, an alkoxide or a siloxane, and specifically can be at least one of aluminum chloride hexahydrate (AlCl3·6H2O), magnesium chloride hexahydrate (MgCl2·6H2O), zirconium oxychloride octahydrate (ZrOCl2·8H2O), lanthanum chloride hexahydrate (LaCl3·6H2O), titanium chloride (TiCl4), hafnium chloride (HfCl4), yttrium acetate (YAc3), zinc acetate dihydrate (ZnAc2·2H2O), tantalum ethoxide (Ta(OC2H5)5), aluminum nitrate nonahydrate, tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), zinc 2-ethylhexanoate, dichloro(bis(diphenylthiourea))cadmium, sodium sulfide and cadmium acetate.

[0034] The embodiment of the present invention screens the filler precursor according to the band gap and dielectric constant values ​​of the inorganic filler to be generated in situ, and requires that it can be uniformly and stably mixed with the polymer matrix in the same solvent, and prepares a polymer-based composite dielectric with uniformly dispersed inorganic fillers by in situ chemical reaction in the polymer matrix.

[0035] In some embodiments, the inorganic filler is at least one of aluminum oxide (Al2O3), magnesium oxide (MgO), zirconium dioxide (ZrO2), lanthanum oxide (La2O3), titanium dioxide (TiO2), hafnium dioxide (HfO2), yttrium oxide (Y2O3), zinc oxide (ZnO), tantalum oxide (Ta2O3), silicon dioxide (SiO2), zinc sulfide, cadmium sulfide, zinc hydroxide and magnesium hydroxide.

[0036] In some embodiments, the solvent is at least one of N,N-dimethylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0037] In some embodiments, the heat treatment process is: under air conditions, the heat treatment temperature is 100° C. to 400° C., and the heat treatment time is 1 hour to 12 hours.

[0038] In some embodiments, the specific steps of coating the mixture solution on a substrate and then subjecting the mixture solution to heat treatment so that the filler precursor generates inorganic fillers in situ in the polymer matrix are as follows: coating the mixture solution on a substrate (preferably a glass substrate), and heat treating the film at a temperature of 100°C to 400°C for 1h to 12h in air conditions so that the filler precursor generates inorganic fillers in situ in the polymer matrix.

[0039] The embodiment of the present invention also provides a polymer-based composite dielectric, wherein the polymer-based composite dielectric is prepared by the preparation method described in any of the above embodiments. The polymer-based composite dielectric comprises a polymer matrix and an inorganic filler, wherein the inorganic filler is dispersed in the polymer matrix with good dispersibility, and the composite dielectric has a high dielectric constant and breakdown strength, breaking through the dielectric-breakdown inverted coupling relationship, and the high-temperature energy storage performance is also significantly improved.

[0040] In some embodiments, the volume fraction of the inorganic filler in the polymer-based composite dielectric material is 0.1% to 3% (for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%). The volume fraction of fillers in existing polymer-based composite dielectrics generally exceeds 5%, and the embodiments of the present invention achieve the inclusion of the low volume fraction of inorganic fillers in the polymer-based composite dielectric, ensuring good dispersibility of the filler and mechanical properties and large-scale processing capabilities of the polymer.

[0041] In this embodiment, the volume fraction of the inorganic filler in the polymer-based composite dielectric material can be calculated based on the raw material feed ratio and relative density.

[0042] In some embodiments, the inorganic filler is nanoparticles, and the average particle size of the nanoparticles is 10 nm to 50 nm.

[0043] An embodiment of the present invention further provides an application of the polymer-based composite dielectric described in any of the aforementioned embodiments in energy storage capacitors, flexible electronic devices or high-frequency circuits.

[0044] The present invention will be further described below by means of specific examples.

[0045] Example 1

[0046] This embodiment provides a method for preparing a PI / ZnO composite dielectric film, comprising the following steps:

[0047] S1, selecting ZnAc2·2H2O as the filler precursor of the inorganic filler ZnO, and selecting aromatic rigid chain polymer polyimide (PI) as the polymer matrix;

[0048] S2, dissolving 500 mg of polymer matrix PI in 20 mL of organic solvent N,N-dimethylpyrrolidone (NMP), stirring at 25°C for 24 h to completely dissolve it; adding 6 mg of filler precursor ZnAc2·2H2O, ultrasonically treating at 25°C for 30 min and stirring for 12 h to obtain a mixture solution;

[0049] S3. The obtained mixture solution is uniformly coated on a clean glass substrate at 25°C, and is placed in an oven for heat treatment at 100°C for 1h, and then at 300°C for 12h, so that the filler precursor ZnAc2·2H2O generates inorganic filler ZnO in situ in the polymer matrix PI to obtain a polymer-based composite film, which is then peeled off from the glass plate and placed in a vacuum oven at 100°C for drying for 24h to obtain a PI / ZnO composite dielectric film with a thickness of about 10μm, wherein the volume fraction of the inorganic filler ZnO in the PI / ZnO composite dielectric film is 0.3%.

[0050] Comparative Example 1

[0051] The preparation method of Comparative Example 1 is the same as that of Example 1, except that 6 mg of ZnO nanopowder (average particle size of 20 nm) is directly used as an inorganic filler to replace the ZnAc2·2H2O filler precursor in Example 1, and finally a PI / ZnO composite dielectric film is obtained.

[0052] Comparative Example 2

[0053] The preparation method of Comparative Example 2 is the same as that of Example 1, except that only the polymer matrix PI is used as the raw material, and the ZnAc2·2H2O filler precursor in Example 1 is omitted, and finally a PI dielectric film is obtained.

[0054] Dielectric and energy storage performance test method of dielectric film: Based on the principle of parallel plate capacitor, the dielectric properties of the prepared dielectric film, including dielectric constant and dielectric loss, were tested using an Agilent E4980A LCR meter. The frequency range was 100Hz to 2MHz, the sample electrode diameter was 6mm, the dielectric constant was converted from the measured capacitance value, and the dielectric loss (tangent angle) was directly given by the instrument. The polarization-electric field strength curve and energy storage density were tested using the American PolyK ferroelectric test station. The test frequency was 100Hz and the sample electrode diameter was 3mm.

[0055] Figure 2 3 is a comparison chart of the energy storage performance of the dielectric films prepared in Example 1, Comparative Example 1 and Comparative Example 2. The results show that at 150°C, the K value of the PI / ZnO composite dielectric film prepared in Example 1 increases from 3.2 of the PI polymer matrix of Comparative Example 2 to 4.2, and is also greater than 4.1 of the PI / ZnO composite dielectric film prepared in Comparative Example 1. The breakdown field strength increases from 300MV / m of the PI polymer matrix of Comparative Example 2 to 400MV / m, and is also greater than 330MV / m of the PI / ZnO composite dielectric film prepared in Comparative Example 1. The energy storage density increases from 0.9J / cm2 of the PI polymer matrix of Comparative Example 2 to 0.6J / cm3 of the PI polymer matrix of Comparative Example 2. 3Increase to 2.5J / cm 3 , and is also greater than 1.5 J / cm of the PI / ZnO composite dielectric film prepared in Comparative Example 1. 3 These data indicate that the polymer-based composite dielectric film prepared by the method of the present invention has both high dielectric constant and breakdown strength, breaks through the dielectric-breakdown inversion coupling relationship, and significantly improves high-temperature energy storage performance.

[0056] Example 2

[0057] This embodiment provides a method for preparing a PI / La2O3 composite dielectric film, comprising the following steps:

[0058] S1, selecting LaCl3·6H2O as a filler precursor of the inorganic filler La2O3, and selecting the same polyimide (PI) as in Example 1 as a polymer matrix;

[0059] S2. Dissolve 500 mg of polymer matrix PI in 20 mL of organic solvent N,N-dimethylpyrrolidone (NMP), and stir at 25°C for 24 h to completely dissolve it; add 6.4 mg of filler precursor LaCl3·6H2O, ultrasonically treat at 25°C for 30 min, and stir for 12 h to obtain a mixture solution;

[0060] S3. The obtained mixture solution is uniformly coated on a clean glass substrate at 25°C, and is placed in an oven for heat treatment at 100°C for 1h, and then at 400°C for 12h, so that the filler precursor LaCl3·6H2O generates inorganic filler La2O3 in situ in the polymer matrix PI to obtain a polymer-based composite film, which is then peeled off from the glass plate and placed in a vacuum oven at 100°C for drying for 24h to obtain a PI / La2O3 composite dielectric film with a thickness of about 10μm, wherein the volume fraction of the inorganic filler La2O3 in the PI / La2O3 composite dielectric film is 0.3%.

[0061] Comparative Example 3

[0062] The preparation method of Comparative Example 3 is the same as that of Example 2, except that 6.9 mg of La2O3 nanopowder (average particle size of 20 nm) is directly used as an inorganic filler to replace the LaCl3·6H2O filler precursor in Example 2, and finally a PI / La2O3 composite dielectric film is obtained.

[0063] The dielectric and energy storage properties of the PI / La2O3 composite dielectric films prepared in Example 2 and Comparative Example 3 were tested using the same test method for dielectric and energy storage properties of dielectric films as described above.

[0064] Figure 3 3 is a comparison chart of the energy storage performance of the dielectric films prepared in Example 2, Comparative Example 2 and Comparative Example 3. The results show that at 150°C, the K value of the PI / La2O3 composite dielectric film prepared in Example 2 increases from 3.2 of the PI polymer matrix of Comparative Example 2 to 4.2, and is also greater than 4.0 of the PI / La2O3 composite dielectric film prepared in Comparative Example 3. The breakdown field strength increases from 300MV / m of the PI polymer matrix of Comparative Example 2 to 540MV / m, and is also greater than 420MV / m of the PI / La2O3 composite dielectric film prepared in Comparative Example 3. The energy storage density increases from 0.9J / cm2 of the PI polymer matrix of Comparative Example 2 to 1.5J / cm3 of the PI polymer matrix of Comparative Example 2. 3 Increased to 4.5 J / cm 3 , and is also greater than 2.2 J / cm of the PI / La2O3 composite dielectric film prepared in Comparative Example 3. 3 These data indicate that the polymer-based composite dielectric film prepared by the method of the present invention has both high dielectric constant and breakdown strength, breaks through the dielectric-breakdown inversion coupling relationship, and significantly improves high-temperature energy storage performance.

[0065] Example 3

[0066] This embodiment provides a method for preparing a PI / ZrO2 composite dielectric film, comprising the following steps:

[0067] S1, selecting ZrOCl2·8H2O as a filler precursor of the inorganic filler ZrO2, and selecting the same polyimide (PI) as in Example 1 as a polymer matrix;

[0068] S2, dissolving 500 mg of polymer matrix PI in 20 mL of organic solvent N,N-dimethylpyrrolidone (NMP), stirring at 25°C for 24 h to completely dissolve it; adding 8.8 mg of filler precursor ZrOCl2·8H2O, ultrasonically treating at 25°C for 30 min and stirring for 12 h to obtain a mixture solution;

[0069] S3. The obtained mixture solution is uniformly coated on a clean glass substrate at 25°C, and placed in an oven for heat treatment at 100°C for 1h, and then heat treated at 400°C for 12h, so that the filler precursor ZrOCl2·8H2O generates inorganic filler ZrO2 in situ in the polymer matrix PI to obtain a polymer-based composite film, which is then peeled off from the glass plate and placed in a vacuum oven at 100°C for drying for 24h to obtain a PI / ZrO2 composite dielectric film with a thickness of about 10μm, wherein the volume fraction of the inorganic filler ZrO2 in the PI / ZrO2 composite dielectric film is 0.3%.

[0070] Comparative Example 4

[0071] The preparation method of Comparative Example 4 is the same as that of Example 3, except that 6.1 mg of ZrO2 nanopowder (average particle size of 20 nm) is directly used as an inorganic filler to replace the ZrOCl2·8H2O filler precursor in Example 3, and finally a PI / ZrO2 composite dielectric film is obtained.

[0072] The dielectric and energy storage properties of the PI / ZrO2 composite dielectric films prepared in Example 3 and Comparative Example 4 were tested using the same test method for dielectric and energy storage properties of dielectric films as described above.

[0073] Figure 4 3 is a comparison chart of the energy storage performance of the dielectric films prepared in Example 3, Comparative Example 2 and Comparative Example 4. The results show that at 150°C, the K value of the PI / ZrO2 composite dielectric film prepared in Example 3 increases from 3.2 of the PI polymer matrix of Comparative Example 2 to 4.3, and is also greater than 4.0 of the PI / ZrO2 composite dielectric film prepared in Comparative Example 4. The breakdown field strength increases from 300MV / m of the PI polymer matrix of Comparative Example 2 to 640MV / m, and is also greater than 450MV / m of the PI / ZrO2 composite dielectric film prepared in Comparative Example 4. The energy storage density increases from 0.9J / cm2 of the PI polymer matrix of Comparative Example 2 to 1.0J / cm3 of the PI polymer matrix of Comparative Example 2. 3 Increased to 6.4 J / cm 3 , and is also greater than 3.0 J / cm of the PI / ZrO2 composite dielectric film prepared in Comparative Example 4. 3 These data indicate that the polymer-based composite dielectric film prepared by the method of the present invention has both high dielectric constant and breakdown strength, breaks through the dielectric-breakdown inversion coupling relationship, and significantly improves high-temperature energy storage performance.

[0074] Example 4

[0075] This embodiment provides a method for preparing a PEI / MgO composite dielectric film, comprising the following steps:

[0076] S1, selecting MgCl2·6H2O as a filler precursor of the inorganic filler MgO, and selecting commercial polymer polyetherimide (PEI) as a polymer matrix;

[0077] S2, dissolving 500 mg of polymer matrix PEI in 20 mL of organic solvent N,N-dimethylpyrrolidone (NMP), stirring at 25°C for 24 h to completely dissolve it; adding 4.2 mg of filler precursor MgCl2·6H2O, ultrasonically treating at 25°C for 30 min and stirring for 12 h to obtain a mixture solution;

[0078] S3. The obtained mixture solution is uniformly coated on a clean glass substrate at 25°C, and is placed in an oven for heat treatment at 100°C for 1h, and then at 400°C for 12h, so that the filler precursor MgCl2·6H2O generates inorganic filler MgO in situ in the polymer matrix PEI to obtain a polymer-based composite film, which is then peeled off from the glass plate and placed in a vacuum oven at 100°C for drying for 24h to obtain a PEI / MgO composite dielectric film with a thickness of about 10μm, wherein the volume fraction of the inorganic filler MgO in the PEI / MgO composite dielectric film is 0.3%.

[0079] Comparative Example 5

[0080] The preparation method of Comparative Example 5 is the same as that of Example 4, except that only the polymer matrix PEI is used as the raw material, and the MgCl2·6H2O filler precursor in Example 4 is omitted, and finally a PEI dielectric film is obtained.

[0081] The dielectric and energy storage properties of the dielectric films prepared in Example 4 and Comparative Example 5 were tested using the same dielectric and energy storage properties testing methods as described above. The results show that at 150°C, the K value of the PEI / MgO composite dielectric film prepared in Example 4 increased from 3.1 of the PEI polymer matrix to 5.2, the breakdown field strength increased from 400MV / m of the PEI polymer matrix to 650MV / m, and the energy storage density increased from 2.0J / cm 3 Increased to 6.6 J / cm 3 These data also illustrate that the polymer-based composite dielectric film prepared by the method of the present invention has both high dielectric constant and breakdown strength, and the high-temperature energy storage performance is also significantly improved.

[0082] Example 5

[0083] This embodiment provides a method for preparing a PC / SiO2 composite dielectric film, comprising the following steps:

[0084] S1. Tetramethoxysilane (TMOS) is selected as the filler precursor of the inorganic filler SiO2, and polycarbonate (PC200) is selected as the polymer matrix;

[0085] S2, dissolving 500 mg of polymer matrix PC200 in 20 mL of organic solvent N,N-dimethylpyrrolidone (NMP), stirring at 25°C for 24 h to completely dissolve it; adding 7.9 mg of filler precursor TMOS, ultrasonically treating at 25°C for 30 min and stirring for 12 h to obtain a mixture solution;

[0086] S3. The obtained mixture solution is uniformly coated on a clean glass substrate at 25°C, and is placed in an oven for heat treatment at 100°C for 1h, and then at 300°C for 12h, so that the filler precursor TMOS generates inorganic filler SiO2 in situ in the polymer matrix PC200 to obtain a polymer-based composite film, which is then peeled off from the glass plate and placed in a vacuum oven at 100°C for drying for 24h to obtain a PC / SiO2 composite dielectric film with a thickness of about 10μm, wherein the volume fraction of the inorganic filler SiO2 in the PC / SiO2 composite dielectric film is 0.3%.

[0087] Comparative Example 6

[0088] The preparation method of Comparative Example 6 is the same as that of Example 5, except that only the polymer matrix PC200 is used as the raw material, and the TMOS filler precursor in Example 5 is omitted, and finally a PC dielectric film is obtained.

[0089] The dielectric and energy storage properties of the dielectric films prepared in Example 5 and Comparative Example 6 were tested using the same dielectric and energy storage properties testing methods as described above. The results showed that at 150°C, the K value of the PC / SiO2 composite dielectric film prepared in Example 5 increased from 2.9 of the PC polymer matrix to 3.4, the breakdown field strength increased from 600MV / m of the PC polymer matrix to 780MV / m, and the energy storage density increased from 4.5J / cm 3 Increased to 7.5 J / cm 3 These data also illustrate that the polymer-based composite dielectric film prepared by the method of the present invention has both high dielectric constant and breakdown strength, and the high-temperature energy storage performance is also significantly improved.

[0090] In summary, the present invention combines a polymer matrix with an organic / inorganic source precursor of a suitable inorganic filler, and the filler precursor undergoes an in-situ chemical reaction in the polymer matrix under heat treatment conditions to generate an inorganic filler, thereby obtaining a polymer-based composite dielectric (the volume fraction of the inorganic filler in the polymer-based composite dielectric material is 0.1% to 3%). The prepared polymer-based composite dielectric has significantly improved dispersibility, breaks through the dielectric-knockdown coupling relationship, significantly improves high-temperature energy storage performance, and is compatible with industrial large-scale production, providing a feasible solution for the research and development of high energy storage density dielectric materials with practical application value.

[0091] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a polymer-based composite dielectric, characterized in that: Includes steps: S1, providing a polymer matrix and a filler precursor; S2, dissolving the polymer matrix in a solvent, adding the filler precursor, and stirring to obtain a mixture solution; S3, coating the mixture solution on a substrate, and then subjecting the substrate to heat treatment so that the filler precursor generates inorganic fillers in situ in the polymer matrix, thereby preparing the polymer-based composite dielectric.

2. The method for preparing a polymer-based composite dielectric according to claim 1, characterized in that: The weight proportion of the filler precursor in the polymer matrix is ​​0.1 wt % to 3 wt %.

3. The method for preparing a polymer-based composite dielectric according to claim 1, characterized in that: The polymer matrix is ​​at least one of polyimide, polyetherimide, polycarbonate, polyfluorene ester, polypropylene, cycloolefin copolymer, polymethyl methacrylate, polyphenylene sulfide, polyamide-imide, polyaryletherurea and polymethylpentene.

4. The method for preparing a polymer-based composite dielectric according to claim 1, characterized in that: The filler precursor is at least one of aluminum chloride hexahydrate, magnesium chloride hexahydrate, zirconium oxychloride octahydrate, lanthanum chloride hexahydrate, titanium chloride, hafnium chloride, yttrium acetate, zinc acetate dihydrate, tantalum ethoxide, aluminum nitrate nonahydrate, tetramethoxysilane, tetraethoxysilane, zinc 2-ethylhexanoate, cadmium dichloride (bis[diphenylthiourea]), sodium sulfide and cadmium acetate; the inorganic filler is at least one of aluminum oxide, magnesium oxide, zirconium dioxide, lanthanum trioxide, titanium dioxide, hafnium dioxide, yttrium trioxide, zinc oxide, tantalum trioxide, silicon dioxide, zinc sulfide, cadmium sulfide, zinc hydroxide and magnesium hydroxide.

5. The method for preparing a polymer-based composite dielectric according to claim 1, characterized in that: The solvent is at least one of N,N-dimethylpyrrolidone, N,N-dimethylformamide and N,N-dimethylacetamide.

6. The method for preparing a polymer-based composite dielectric according to claim 1, characterized in that: The heat treatment process is as follows: under air conditions, the heat treatment temperature is 100° C. to 400° C., and the heat treatment time is 1 hour to 12 hours.

7. A polymer-based composite dielectric, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 6.

8. The polymer-based composite dielectric according to claim 7, characterized in that: The polymer-based composite dielectric comprises a polymer matrix and an inorganic filler, wherein the volume fraction of the inorganic filler in the polymer-based composite dielectric is 0.1% to 3%.

9. The polymer-based composite dielectric according to claim 7, characterized in that: The inorganic filler is nanoparticles, and the average particle size of the nanoparticles is 10nm to 50nm.

10. Use of the polymer-based composite dielectric according to any one of claims 7 to 9 in energy storage capacitors, flexible electronic devices or high-frequency circuits.

Citation Information

Patent Citations

  • High-temperature energy storage hybrid polyetherimide dielectric film and preparation method and application thereof

    CN112789326A

Cited By

  • Preparation method of all-organic micromolecule composite polymer film and product

    CN121378825A